PENERAPAN PERANGKAT MULTIMEDIA DALAM PEMBELAJARAN BERBASIS DIGITAL UNTUK MENINGKATKAN LITERASI SISWA TINGKAT MADRASAH IBTIDAIYAH - Firdaus Ainul Yaqin (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
The role of ICT (Information and Communication Technology) in the world of education is very large in terms of the benefits and advantages it has, namely facilitating broad access to education, being able to improve the quality as well as the quality of learning between teachers and students. ICT must be mastered by teachers and become a matter of priority that must really be understood by every teacher as a competency standard in the current era. The use of ICT-based learning media is expected to make it easier for students to understand and accept the learning process carried out by the teacher. Through Movie Maker, a teacher can easily develop learning media to suit the situation, conditions and environment of students. This animated learning media can represent the presence of teachers when they cannot meet face to face in class during a pandemic or certain situations that do not allow face to face meetings. Keywords: Movie Maker, ICT learning media, Media